6/z-2=-5/3z+4

Simple and best practice solution for 6/z-2=-5/3z+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6/z-2=-5/3z+4 equation:



6/z-2=-5/3z+4
We move all terms to the left:
6/z-2-(-5/3z+4)=0
Domain of the equation: z!=0
z∈R
Domain of the equation: 3z+4)!=0
z∈R
We get rid of parentheses
6/z+5/3z-4-2=0
We calculate fractions
18z/3z^2+5z/3z^2-4-2=0
We add all the numbers together, and all the variables
18z/3z^2+5z/3z^2-6=0
We multiply all the terms by the denominator
18z+5z-6*3z^2=0
We add all the numbers together, and all the variables
23z-6*3z^2=0
Wy multiply elements
-18z^2+23z=0
a = -18; b = 23; c = 0;
Δ = b2-4ac
Δ = 232-4·(-18)·0
Δ = 529
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$z_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$z_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{529}=23$
$z_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(23)-23}{2*-18}=\frac{-46}{-36} =1+5/18 $
$z_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(23)+23}{2*-18}=\frac{0}{-36} =0 $

See similar equations:

| 5x^2-35x-6=0 | | 21x+6=48 | | 2.5x-3.5=x+1 | | 2.5x+1.5=2x+5 | | 1.5x+3=2x-2 | | 8(0)-y=4 | | 3/2x-2=x+2 | | 8x-0=4 | | |5x-3|=10 | | 3.3=8.8-2.5x | | 4.5z=4.5-4.5+6.25 | | 10x²-19+6=0 | | 10x²-19+16=0 | | 3p/5=10 | | 8(x+5)=-4(x+8 | | 8(x+5)=-4(x-8) | | y+1/12=3/4 | | 30x+3=74 | | 74x-30=3 | | X=x2+6x+9÷3x+15 | | 2x-5/x+7=7 | | 74x-3=30 | | 5/x=-35/43 | | 30x-3=74 | | 6x-12-x=9x+53+× | | 12+1.50x=72 | | -x+15=10 | | 4(3m+2)=5 | | 4(-x+2)=-(x-4) | | -x-2(0)=2 | | 4y=-24y= | | -24=2(x-7)+6 |

Equations solver categories